Quasi-Clusters in Nuclear Photodisintegration in the Giant Dipole Resonance Region (Global Journal of Science Frontier Research, 2022)
The role of quasi-clusters systems of a small number of nucleons in the photodisintegration of light atomic nuclei of the -shell is considered In these nuclei there is a strong supermultiplet splitting of levels due to the prominent role of the Majorana forces It is manifested in the excitation and decay of the Giant Dipole Resonance GDR leading to its large-scale configurational splitting Nucleon quartets formed inside the nucleus have a powerful effect on the properties of the GDR of 1p-shell nuclei The preservation or decay of such quartets during nuclear photoabsorption leads to the formation of various GDR regions Experimental data confirming this phenomenon are presented
Keywords: giant dipole resonance; shell nuclei; configurational splitting; supermultiplet structure; Majorana forces; Young schemes; nucleon quartets